Canine Vaginal Cytology: A Revised Definition of Exfoliated Vaginal Cells - Reckers, Felix; Klopfleisch, Robert; Belik, Vitaly; Arlt, Sebastian (Frontiers in Veterinary Science, 2022)
Vaginal cytology is an important examination method in the context of gynaecological disorders and cycle staging in the bitch. While collection and preparation of samples are easy, the evaluation appears to be challenging. Inconsistent definitions of cell attributes such as size, cornification and the appearance of the nucleus have been published. The aim of the project was to develop a tutorial for vaginal cell determination. To get a deeper insight into the use of cytology in practice, an online survey was distributed to veterinarians interested in small animal reproduction. Participants were asked to define eight cells and answer questions. The agreement of the sixteen participants, working in eight different countries, determining the cells was poor (κ= 0.412). Eleven respondents stated that vaginal cytology has a low reliability. Nevertheless, thirteen participants use this tool regularly. The tutorial was developed as a flowchart based on the survey results, scientific literature and own measurements. It guides the user systematically through the evaluation of specific cell characteristics. An evaluation of the results of five raters with difference experience levels led to a high agreement (κ=0.858). Vaginal cytology is a useful diagnostic tool, but it seems helpful to standardize the determination of cell types.